Biochar promotes arsenic (As) immobilization in contaminated soils and alleviates the As-toxicity in soybean (Glycine max (L.) Merr.). (April 2022) - Hakeem, Khalid Rehman; Alharby, Hesham F.; Bamagoos, Atif A.M.; Pirzadah, Tanveer Bilal
Abstract: Pot experiments were carried out to examine the biochar application and its alleviating effect on arsenic (As) toxicity in soybean plants. The data showed that As inhibits the growth indices and it increased with enhanced As-concentration in the substrate. The growth indices declined by more than 40% and the osmolyte concentration, photosynthetic pigments and antioxidant enzymes were decreased significantly among As-stressed plants. However, biochar application effectively mitigated the inhibitory effects of As on the soybean growth and the mitigation effect of treatment is more prevalent to the plants subjected to higher As-treatment. Biochar significantly reduced the As-uptake as revealed by the translocation factor (<1), indicating more As is restrained in the roots. The reduction in the total chlorophyll and carotenoid content was found less in the As-treated soybean plants upon biochar application. Similarly, the osmolytes comprising proline, sugar and protein increased upon application of biochar. The biomarkers viz., membrane stability index (MSI), hydrogen peroxide and malondialdehyde (MDA) content significantly decreased at higher As-levels upon biochar application as was also supported by the heatmap analysis. Moreover, the antioxidative enzymes also showed a significant increase upon addition of biochar. Our data showed that biochar amendment effectively alleviates the As-stress by enhancing the sorption of As in the substrate thus, significantly declining the As concentration in plant leaves, and thus the results of the current study depicting the role of biochar as a promising, cost-effective and eco-friendly amendment to decontaminate the As-polluted soils. Graphical abstract: Image 1 Highlights: Biochar greatly alleviates the phytotoxicity of arsenic (As) to soybean plants. Reduced As bioavailability by biochar offsets its negative effect on plant growth. Biochar application accelerates the defense system of soybean plants by enhancing their antioxidant enzyme activities. The biochar could serve as an eco-friendly amendment for mitigating the As-pollution in the soil-grain system.